Methodological principles of control of future qualified workers’ learning achievements - Man’ko, V (Professional Pedagogics, 2011)
The article investigates theoretical aspects of establishing the complexity of learning actions. On the basis of the theory of stage-by-stage formation of intellectual actions indicators of description of learning actions in the sequence of their formation are singled out.